Broadband macroscopic cortical oscillations emerge from intrinsic neuronal response failures - Goldental, Amir; Vardi, Roni; Sardi, Shira; Sabo, Pinhas; Kanter, Ido (Frontiers in Neural Circuits, 2015)
Broadband spontaneous macroscopic neural oscillations are rhythmic cortical firing which was extensively examined during the last century, however, their possible origination is still controversial. In this work we show how macroscopic oscillations emerge in solely excitatory random networks and without topological constraints. We experimentally and theoretically show that these oscillations stem from the counterintuitive underlying mechanism - the intrinsic stochastic neuronal response failures. These neuronal response failures, which are characterized by short-term memory, lead to cooperation among neurons, resulting in sub- or several- Hertz macroscopic oscillations which coexist with high frequency gamma oscillations. A quantitative interplay between the statistical network properties and the emerging oscillations is supported by simulations of large networks based on single-neuron in-vitro experiments and a Langevin equation describing the network dynamics. Results call for the examination of these oscillations in the presence of inhibition and external drives.